Kebijakan Perguruan Tinggi Negeri Yogyakarta Terhadap Penyandang Disabilitas - Akhmad Soleh (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
This study discusses the accessibility of university education in the four public universities in Yogyakarta; Indonesian Arts Institute (ISI), University of Gajah Mada (UGM),Yogyakarta State University (UNY), and State Islamic University (UIN) Sunan Kalijaga. Upto now, the disability groups have not got an equal access and the opportunity in a higher education. There are only a few students with disabilities that are accepted in Universities in Indonesia, because of physical limitations that would interfere the teaching-learning process in their classrooms. The research findings showed that the education systems in the UGM, Yogyakarta State University, and the ISI have a system of "integration", while at UIN has led to the inclusion system, that is "accommodative" and has the ability to service for persons with disabilities.